Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's determine which pairs of expressions are equivalent for [tex]\( y = 2 \)[/tex] and [tex]\( y = 5 \)[/tex].
### Step-by-Step Analysis
1. First Pair: [tex]\( 2y - 1 \)[/tex] and [tex]\( 3y - 5 + y \)[/tex]
- For [tex]\( y = 2 \)[/tex]:
- [tex]\( 2y - 1 = 2(2) - 1 = 4 - 1 = 3 \)[/tex]
- [tex]\( 3y - 5 + y = 3(2) - 5 + 2 = 6 - 5 + 2 = 3 \)[/tex]
- For [tex]\( y = 5 \)[/tex]:
- [tex]\( 2y - 1 = 2(5) - 1 = 10 - 1 = 9 \)[/tex]
- [tex]\( 3y - 5 + y = 3(5) - 5 + 5 = 15 - 5 + 5 = 15 \)[/tex]
Since [tex]\( 2y - 1 = 3y - 5 + y \)[/tex] for [tex]\( y = 2 \)[/tex] but not for [tex]\( y = 5 \)[/tex], these expressions are not equivalent.
2. Second Pair: [tex]\( 5y + 4 \)[/tex] and [tex]\( 7y + 4 - 2y \)[/tex]
- For [tex]\( y = 2 \)[/tex]:
- [tex]\( 5y + 4 = 5(2) + 4 = 10 + 4 = 14 \)[/tex]
- [tex]\( 7y + 4 - 2y = 7(2) + 4 - 2(2) = 14 + 4 - 4 = 14 \)[/tex]
- For [tex]\( y = 5 \)[/tex]:
- [tex]\( 5y + 4 = 5(5) + 4 = 25 + 4 = 29 \)[/tex]
- [tex]\( 7y + 4 - 2y = 7(5) + 4 - 2(5) = 35 + 4 - 10 = 29 \)[/tex]
Since [tex]\( 5y + 4 = 7y + 4 - 2y \)[/tex] for both [tex]\( y = 2 \)[/tex] and [tex]\( y = 5 \)[/tex], these expressions are equivalent.
3. Third Pair: [tex]\( y + 7 \)[/tex] and [tex]\( y + 2 + y \)[/tex]
- For [tex]\( y = 2 \)[/tex]:
- [tex]\( y + 7 = 2 + 7 = 9 \)[/tex]
- [tex]\( y + 2 + y = 2 + 2 + 2 = 6 \)[/tex]
- For [tex]\( y = 5 \)[/tex]:
- [tex]\( y + 7 = 5 + 7 = 12 \)[/tex]
- [tex]\( y + 2 + y = 5 + 2 + 5 = 12 \)[/tex]
Since [tex]\( y + 7 \neq y + 2 + y \)[/tex] for [tex]\( y = 2 \)[/tex] but they equal for [tex]\( y = 5 \)[/tex], these expressions are not equivalent.
4. Fourth Pair: [tex]\( 3y - 4 \)[/tex] and [tex]\( 3y - 2 + y \)[/tex]
- For [tex]\( y = 2 \)[/tex]:
- [tex]\( 3y - 4 = 3(2) - 4 = 6 - 4 = 2 \)[/tex]
- [tex]\( 3y - 2 + y = 3(2) - 2 + 2 = 6 - 2 + 2 = 6 \)[/tex]
- For [tex]\( y = 5 \)[/tex]:
- [tex]\( 3y - 4 = 3(5) - 4 = 15 - 4 = 11 \)[/tex]
- [tex]\( 3y - 2 + y = 3(5) - 2 + 5 = 15 - 2 + 5 = 18 \)[/tex]
Since [tex]\( 3y - 4 \neq 3y - 2 + y \)[/tex] for both [tex]\( y = 2 \)[/tex] and [tex]\( y = 5 \)[/tex], these expressions are not equivalent.
### Conclusion
The only pair of expressions that is equivalent for both given values of [tex]\( y \)[/tex] is:
[tex]\[ 5y + 4 \quad \text{and} \quad 7y + 4 - 2y \][/tex]
### Step-by-Step Analysis
1. First Pair: [tex]\( 2y - 1 \)[/tex] and [tex]\( 3y - 5 + y \)[/tex]
- For [tex]\( y = 2 \)[/tex]:
- [tex]\( 2y - 1 = 2(2) - 1 = 4 - 1 = 3 \)[/tex]
- [tex]\( 3y - 5 + y = 3(2) - 5 + 2 = 6 - 5 + 2 = 3 \)[/tex]
- For [tex]\( y = 5 \)[/tex]:
- [tex]\( 2y - 1 = 2(5) - 1 = 10 - 1 = 9 \)[/tex]
- [tex]\( 3y - 5 + y = 3(5) - 5 + 5 = 15 - 5 + 5 = 15 \)[/tex]
Since [tex]\( 2y - 1 = 3y - 5 + y \)[/tex] for [tex]\( y = 2 \)[/tex] but not for [tex]\( y = 5 \)[/tex], these expressions are not equivalent.
2. Second Pair: [tex]\( 5y + 4 \)[/tex] and [tex]\( 7y + 4 - 2y \)[/tex]
- For [tex]\( y = 2 \)[/tex]:
- [tex]\( 5y + 4 = 5(2) + 4 = 10 + 4 = 14 \)[/tex]
- [tex]\( 7y + 4 - 2y = 7(2) + 4 - 2(2) = 14 + 4 - 4 = 14 \)[/tex]
- For [tex]\( y = 5 \)[/tex]:
- [tex]\( 5y + 4 = 5(5) + 4 = 25 + 4 = 29 \)[/tex]
- [tex]\( 7y + 4 - 2y = 7(5) + 4 - 2(5) = 35 + 4 - 10 = 29 \)[/tex]
Since [tex]\( 5y + 4 = 7y + 4 - 2y \)[/tex] for both [tex]\( y = 2 \)[/tex] and [tex]\( y = 5 \)[/tex], these expressions are equivalent.
3. Third Pair: [tex]\( y + 7 \)[/tex] and [tex]\( y + 2 + y \)[/tex]
- For [tex]\( y = 2 \)[/tex]:
- [tex]\( y + 7 = 2 + 7 = 9 \)[/tex]
- [tex]\( y + 2 + y = 2 + 2 + 2 = 6 \)[/tex]
- For [tex]\( y = 5 \)[/tex]:
- [tex]\( y + 7 = 5 + 7 = 12 \)[/tex]
- [tex]\( y + 2 + y = 5 + 2 + 5 = 12 \)[/tex]
Since [tex]\( y + 7 \neq y + 2 + y \)[/tex] for [tex]\( y = 2 \)[/tex] but they equal for [tex]\( y = 5 \)[/tex], these expressions are not equivalent.
4. Fourth Pair: [tex]\( 3y - 4 \)[/tex] and [tex]\( 3y - 2 + y \)[/tex]
- For [tex]\( y = 2 \)[/tex]:
- [tex]\( 3y - 4 = 3(2) - 4 = 6 - 4 = 2 \)[/tex]
- [tex]\( 3y - 2 + y = 3(2) - 2 + 2 = 6 - 2 + 2 = 6 \)[/tex]
- For [tex]\( y = 5 \)[/tex]:
- [tex]\( 3y - 4 = 3(5) - 4 = 15 - 4 = 11 \)[/tex]
- [tex]\( 3y - 2 + y = 3(5) - 2 + 5 = 15 - 2 + 5 = 18 \)[/tex]
Since [tex]\( 3y - 4 \neq 3y - 2 + y \)[/tex] for both [tex]\( y = 2 \)[/tex] and [tex]\( y = 5 \)[/tex], these expressions are not equivalent.
### Conclusion
The only pair of expressions that is equivalent for both given values of [tex]\( y \)[/tex] is:
[tex]\[ 5y + 4 \quad \text{and} \quad 7y + 4 - 2y \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.